Use of sulfosalicylic acid in the detection of proteinuria and its application to hypertensive problems in pregnancy (2011)
ABSTRACT: To determine the reliability and accuracy of the sulfosalicylic acid test in the fast detection and semi-quantitative analysis of proteinuria. Methods: Prospective, descriptive study at Hospital Universitario San Vicente de Paúl in Medellín, Colombia. Ninety eight women with proteinuria and 129 without it were included. Turbidity test with sulfosalicylic acid was compared to 24-hour-proteinuria. Results: The likelihood ratios (LR) for turbidity test results of 1+, 2+, 3+, 4+, and 5+ were 0.4, 0.7, 3.4, 6.7, and 39.1, respectively. Interclass correlation between the three evaluators of turbidity was 0.966. With the cut point set at 4+, sensitivity was 41.1% (CI 95%: 30.6-51.5), and specificity was 97.7% (CI 95%: 94.7-100). In hypertensive patients, positive predictive value was 95% (CI 95%: 87-100) and negative predictive value was 53.3% (CI 95%: 42.5-64). Conclusion: Turbidity test is an easy, fast, cheap, and reproducible analysis. Because of its high specificity it is ideal to study pregnant women, particularly those with hypertension, for proteinuria.